PENGARUH KEMAMPUAN DOSEN MELAKSANAKAN EVALUASI TERHADAP KEAKTIFAN BELAJAR MAHASISWA PADA MATA KULIAH ANALISIS KOMPLEKS PROGRAM STUDI TADRIS MATEMATIKA IAIN PADANGSIDIMPUAN - Adinda, Anita (IAIN PADANGSIDIMPUAN, 2018)
This study aims to study how to facilitate student learning in complex analysis courses in mathematics study program at IAIN Padangsidimpuan. The population of this study is the sixth semester students of the IAIN Padangsidimply mathematics mathematics study program 2017/2018 academic year. The sampling technique was done by cluster random sampling, namely the semester VI TMM-1 which passed 27 people in the mathematics study program IAIN Padangsidimpuan. The research method used by the writer is descriptive method. The data collection techniques in this study were questionnaires (questionnaires). The data obtained were analyzed using hypotheses using the Pearson Product Moment estimation formula and to find out whether there was a significant effect using the